Congenital hyperinsulinism in clinical practice: From biochemical pathophysiology to new monitoring techniques - Martino, Mariangela; Sartorelli, Jacopo; Gragnaniello, Vincenza; Burlina, Alberto (Frontiers in Pediatrics, 2022)
Congenital hyperinsulinism comprises a group of diseases characterized by a persistent hyperinsulinemic hypoglycemia, due to mutation in the genes involved in the regulation of insulin secretion. The severity and the duration of hypoglycemic episodes, primarily in the neonatal period, can lead to neurological impairment. Detecting blood sugar is relatively simple but, unfortunately, symptoms associated with hypoglycemia may be nonspecific. Research in this field has led to novel insight in diagnosis, monitoring and treatment, leading to a better neurological outcome. Given the increased availability of continuous glucose monitoring systems that allow glucose level recognition in a minimally invasive way, monitoring the glycemic trend becomes easier and there are more possibilities of a better follow-up of patients. We aim to provide an overview of new available technologies and new discoveries and their potential impact on clinical practice, convinced that only with a better awareness of the disease and available tools can we have a better impact on CHI diagnosis, prevention and clinical sequelae.